Antimicrobial analysis of Mikania glomerata extract (Research, Society and Development, 2021)
The treatment and cure of various infections suffered great advances after the discovery of antimicrobials, however the indiscriminate use of these drugs caused bacterial resistance, triggering public health problems such as increased treatment costs. Among the search for new effective and safe therapeutic alternatives is the use of herbal medicines. The work aimed to evaluate in vitro the antimicrobial potential of the extract of Mikania glomerata (guaco) through the Minimum Inhibitory Concentration and Minimum Bactericidal Concentration. The microdilution technique was performed in order to determine the efficacy of the hydroalcoholic extract of Mikania glomerata against the standard strains of Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC25923). Thus, it was found that the extract showed antimicrobial activity for the gram-positive bacteria Staphylococcus aureus (ATCC 25923) and for the gram-negative bacteria Escherichia coli (ATCC 25922). The hydroalcoholic extract of Mikania glomerata was shown to be active with inhibition of microbial growth in varying concentrations in relation to all the microorganisms used in the study, with the antimicrobial activity of the extract possibly attributed to the existence of active compounds such as kaurenic acid and cinamolgrandifloric acid.